Electric vehicle (EV) charging/discharging station (EVCDS)-II : charging/discharging controller design - Koh, Kok Siang (2015)
Singapore has acceded to the Kyoto Protocol of United Nations Framework Convention on Climate Change on 12 April 2006. Since then, it has taken action to cut down on carbon dioxide (CO2) emission. In 2011, the government is carrying out a three years test-bedding program to determine if a large-scale adoption of electric vehicles (EV) is sustainable both economically and environmentally. A sum of $20 million is set aside for the trial. The key features of electric vehicles are it offers a greener and cleaner alternative to the traditional petrol and diesel-based automobiles. On the other hand, the EV can be utilized as a backup for power grid when the energy stored in the battery is discharge from the Vehicle-to-Grid (V2G). However, due to its high cost and low driving range, it remains unpopular among the automobile owners. Also, the faster charging time of electric vehicles is about 30 minutes compared to petrol-based vehicles which required 5 minutes. One of the ways to overcome this problem is the swapping of battery system used in Germany and Japan. In this project, the EV Charging/Discharging Station consists of a Charging/Discharging Network (CDN) and an Intelligent Metering/Payment Network (IMPN). The CDN includes a DC/DC booster, a charging/discharging controller and a DC/AC bidirectional converter. The MPN includes a two way time-of-use meter, a cash/credit card payment subsystem, a website, a communication network and a central server.